دور برامج سياسة التحفيز الجبائي في تطوير المؤسسات الصغيرة والمتوسطة بالجزائر دراسة حالة الوكالة الوطنية لتطوير الاستثمار Andi 2002-2012 - بوقفة, عبد الحق; رزيق, كمال (جامعة الوادي - University of Eloued, 2013)
تهدف هذه الدراسة إلى معرفة مدى مساهمة سياسة التحفيز الجبائي التي تقدمها الدولة من خلال مختلف الإجراءات والقوانين التشريعية والتنظيمية عن طريق الوكالة الوطنية لتطوير الاستثمار ANDI في تطوير المؤسسات الصغيرة والمتوسطة بالجزائر، وقسمت هذه الدراسة إلى جزئيين رئيسيين، الجزء الأول الذي تم من خلاله تقديم البناء النظري حول الموضوع أما الجزء الثاني فقد خصص للدراسة التطبيقية التي تناولت دراسة دور برامج التحفيز الجبائي المقدم من طرف ANDI في تطوير المؤسسات الصغيرة والمتوسطة بالجزائر. تم التوصل من خلال هذه الدراسة إلى نتائج أهمها أن أحجام المؤسسات الصغيرة والمتوسطة عرفت تطورات عديدة شملت زيادة على مستويات الاستثمارات بها وكذلك زيادة على مستويات التشغيل بهذه المؤسسات. The aim of this study was to investigate the contribution of fiscal stimulus policy advanced by the State through the various procedures and legislative and regulatory acts by the National Agency for Investment Development ANDI in the development of small and medium-sized enterprises in Algeria. And divided this study to two parts major, the first part from which the offer constructive theoretical on the subject, and the second part was dedicated to the study of applied study. examined the role of fiscal stimulus programs sponsored by the ANDI in the development of small and medium-sized enterprises in Algeria. Results was reached that the most important sizes small and medium-sized enterprises known many developments, including increased levels of investment as well as increased levels of operating these institutions.
مقال
Keywords: الاقتطاع الجبائي، التحفيز الجبائي، المؤسسات الصغيرة والمتوسطة; fiscal stimulus, small and medium-sized enterprises.